Iron Supply Pathways Between the Surface and Subsurface Waters of the Southern Ocean: From Winter Entrainment to Summer Storms. Issue 24 (17th December 2019) - Nicholson, S.‐A.; Lévy, M.; Jouanno, J.; Capet, X.; Swart, S.; Monteiro, P. M. S.
Abstract: Dissolved iron (DFe) plays an immeasurable role in shaping the biogeochemical processes of the open‐ocean Southern Ocean. However, due to observational constraints iron supply pathways remain poorly understood. Using an idealized eddy‐resolving physical‐biogeochemical model representing a turbulent sector of the Southern Ocean with seasonal buoyancy forcing and zonal winds overlaid by storms, we quantify the importance of a range of subsurface and surface iron supply mechanisms. The main physical supply pathways to the surface layer are via eddy advection and winter convective mixing in equal proportions. The associated subsurface loss of DFe is restocked via net remineralization (75%) and eddy advection (25%). Summer storms resulted in weak DFe supplies relative to the seasonal supplies (<7.6%). However, in situations of deep summer mixed layers and when interacting with underlying ocean fronts, summer storms resulted in enhanced diffusive and advective DFe supplies and raised summer primary production by 20% for several days. Plain Language Summary: The surface of the Southern Ocean is iron depleted, which strongly limits the amount of phytoplankton growth that can occur. Every year, deep mixing in winter moves large quantities of iron from a subsurface underutilized iron reservoir to the surface alleviating the iron limitation. Once there is sufficient light in spring, phytoplankton consume this iron supply leaving the summer months iron depleted. How exactly phytoplankton are supported through the summer when iron limitations are strong remains under question. This study uses a numerical model to simulate the seasonal and intraseasonal iron supply pathways. We show that physical supplies via advection by eddies and winter mixing drive surface seasonal supplies in equal proportions. During summer, storms supply iron via intermittent mixing and thus increase primary production, particularly over regions of strong ocean fronts. Key Points: Eddy advection and winter mixing support annual surface iron supplies in equal proportion in an eddy‐resolving model Eddy advection contributes 25% to restocking subsurface iron reservoir in addition to 75% by local recycling Storms are the most efficient in increasing iron supplies in early summer and over ocean fronts